2015
DOI: 10.1177/0008417414561857
|View full text |Cite
|
Sign up to set email alerts
|

Assessment practices of Canadian occupational therapists working with adults with mental disorders

Abstract: Despite wide variations in occupational therapists' assessment practices, the use of standardized assessments is prevalent. The low rate of repeated measures (0% to 25.9%) suggests a need to better monitor changes and treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
3
4
0
4
Order By: Relevance
“…Surprisingly, these results showed that COPM proportion was more important than years of experience. Many other researchers have found that COPM use depends on the occupational therapist (Donnelly et al, 2017;Rouleau et al, 2015;Toomey et al, 1995). The present study's findings support these results.…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, these results showed that COPM proportion was more important than years of experience. Many other researchers have found that COPM use depends on the occupational therapist (Donnelly et al, 2017;Rouleau et al, 2015;Toomey et al, 1995). The present study's findings support these results.…”
Section: Discussionsupporting
confidence: 90%
“…Or, l’évaluation peu fréquente des aptitudes psychologiques, émotionnelles et socioculturelles ainsi que de la spiritualité, des sous-composantes de la personne dont l’ergothérapeute doit tenir compte (OEQ, 2016b), est préoccupante. Ces résultats sont toutefois similaires à ceux d’autres études canadiennes, dont celle de Rouleau et collaborateurs (2015) issue du domaine de la santé mentale. Une autre étude réalisée auprès d’aînés en réadaptation à la suite d’un accident vasculaire cérébral (AVC) et leur proche-aidant a par ailleurs rapporté un manque de soutien psychologique (Talbot et al, 2004).…”
Section: Discussionunclassified
“…Quelques études menées au Canada et au Québec ont permis d’explorer les pratiques des ergothérapeutes. Réalisées dans différents contextes de pratique très spécifiques tels qu’à l’urgence, en santé mentale ou auprès de personnes ayant des déficits cognitifs, les études rapportaient généralement une grande variabilité des pratiques ergothérapiques (Belchior, Korner-Bitensky, Holmes et Robert, 2015; Douglas, Liu, Warren et Hopper, 2007; Korner-Bitensky, Barrett-Bernstein, Bibas et Poulin, 2011; Rouleau, Dion et Korner-Bitensky, 2015) ainsi qu’une large utilisation de méthodes d’évaluation non standardisées (Belchior et al, 2015; Douglas et al, 2007; Korner-Bitensky et al, 2011; Rouleau et al, 2015; Veillette, Demers et Dutil, 2007). Selon Douglas et collaborateurs (2007), les ergothérapeutes travaillant auprès des aînés présentant des atteintes cognitives utilisent une approche globale du fonctionnement, les tâches de la vie quotidienne et de cuisine étant leurs principales cibles d’évaluation.…”
unclassified
See 1 more Smart Citation
“…Of the occupational therapists who carried out occupational therapy interventions, 41% ( n = 45) of the respondents didn’t measure the outcome of the occupational therapy intervention. Previous studies have also showed that occupational therapists have difficulties using and repeating outcome measures in mental health and other settings (Rouleau et al., 2015; Samsonraj et al., 2012). This lack of outcome measurement will be a barrier to demonstrating the benefits of occupational therapy interventions to service users, managers and commissioners as well as a barrier to intervention research.…”
Section: Critical Reflection On Practicementioning
confidence: 99%